Preliminary Insights into Summer Archaeal Communities in Eutrophic Jinhae Bay, Korea - Jae-Hyun Lim; Sang-Pil Yoon (Diversity, 2025)
Marine archaea play crucial roles in global biogeochemical cycles and climate regulation, yet their ecological functions in many coastal environments remain poorly understood. Jinhae Bay (JB), a eutrophic and environmentally stressed coastal system in Korea, has attracted growing attention; however, its archaeal community composition has not been characterized. In this preliminary study, we investigated the summer archaeal community structure in JB water columns based on a survey conducted in July 2018. We identified 5 archaeal phyla—primarily Euryarchaeota and Thaumarchaeota—along with 11 classes and 18 orders, with Nitrosopumilales and Methanobacteriales as dominant orders. Several ammonia-oxidizing archaea (AOA), including Candidatus Nitrosopumilus adriaticus, Candidatus Nitrosopumilus salaria, Candidatus Nitrosopumilus sediminis, and unclassified Nitrosopumilus spp., were detected. Additionally, the presence of methane-oxidizing archaea (MOA) such as Candidatus Methanoperedens nitroreducens, although at low relative abundance, suggests potential roles in nitrogen and methane cycling. These findings provide initial insights into the archaeal contributions to biogeochemical processes in JB, highlighting the need for further seasonal and functional investigations.